Dynamics of body calcium and net calcium requirements for maintenance of Saanen goats - Dorigan, C. J. [UNESP]; Vargas, J. A. C. [UNESP]; Haerter, C. J. [UNESP]; Resende, K. T. [UNESP]; Vitti, D. M. S. S.; Abdalla, A. L.; Teixeira, I. A. M. A. [UNESP] (Cambridge Univ Press, 2018)
The objectives of the current study were to investigate the dynamics of body calcium (Ca) and to estimate the net Ca maintenance requirements (NCam) of Saanen goats, using Ca-45 as a radiotracer. Eighteen castrated male Saanen goats (25 +/- 2.3 kg body weight (BW)) received a basal diet (ground ear maize, ground maize and vitamin-mineral premix). The treatments consisted of adding limestone to the basal diet to provide Ca content of 0.6, 1.7 and 3.0 g/kg dry matter (DM). The experiment lasted 45 days (i.e. 36 d of adaptation and 9 days of measurements). On day 38, 0.5 ml of 7.4 MBq Ca-45 solution was administrated before feeding. From days 39 to 45, samples of faeces, blood and urine were collected, and Ca concentration determined. The Ca intake, Ca in faeces, Ca in urine, faecal endogenous Ca and true absorbed Ca increased linearly as Ca content in the diets increased, while retained Ca increased at a decreasing rate. Dry matter intake decreased at an increasing rate with increased Ca content in the diets. In contrast, Ca content in the diets did not affect biological availability of Ca, or Ca in plasma. The true biological availability of Ca from limestone in Saanen goats was 0.72. The daily NCam was 11.6 (+/- 1.3) mg/kg BW. The current results might help to understand Ca dynamics in goats and enhance the formulation of balanced diets to best meet Ca requirements of Saanen goats.
Keywords: Faecal endogenous Ca; goat; isotopic dilution method; maintenance requirement